Fast‐Forward to Perturbed Equilibrium Climate. Issue 15 (5th August 2019) - Saint‐Martin, D.; Geoffroy, O.; Watson, L.; Douville, H.; Bellon, G.; Voldoire, A.; Cattiaux, J.; Decharme, B.; Ribes, A.
Abstract: The equilibrium climate sensitivity, that is, the global‐mean surface‐air temperature change in response to a doubling of the carbon dioxide concentration is a widely used metric in climate change studies. Its exact value is rarely known because its estimation requires a long integration time of several thousand years. We propose a method to estimate an accurate value of the equilibrium response from fully coupled climate models at a reasonable computational cost. Using this method, our state‐of‐the‐art climate model CNRM‐CM6‐1 reaches a stationary state after only few hundred of years of integration. This "Fast‐Forward" method consists of an optimal two‐step forcing pathway designed using the framework of a two‐layer energy balance model. It can be applied easily to any coupled climate model. Key Points: A simple method for estimating the equilibrium climate sensitivity is proposed The method allows to simulate the stationary climate corresponding to any given radiative perturbation with a limited computational cost The method can be applied to any atmosphere‐ocean coupled climate model